Dynamic mechanical behavior of additively manufactured bio-inspired metallic lattice structure subjected to high strain rate impact loading - Song, Weidong; Feng, Genzhu; Yu, Guoji; Shi, Gaoquan; Xiao, Lijun (International journal of impact engineering, 2023)
•The auxeticity of the sponge lattice structure can be affected by the loading velocities.•The mechanical response of sponge lattice structure is more stable compared with frame lattice structure.•Sponge lattice structure and frame lattice structure exhibit obvious impact velocity sensitivity. The bio-inspired sponge lattice structure (SLS) and frame lattice structure (FLS) are fabricated by laser powder bed fusion using 316 L stainless steel. The static and dynamic mechanical behavior of the two structures is investigated experimentally by universal testing machine and direct impact Hopkinson bar (DIHB) devices respectively. The deformation evolution of the structures is also captured by the digital camera. Meanwhile, numerical simulations are performed by ABAQUS to further explore the mechanical properties of the lattices. Subsequently, the influence of impact velocity on the deformation modes and specific plateau stress of the lattice structures is investigated. The results show that the SLS presents a stable mechanical response under both quasi-static and dynamic loadings compared with the FLS, while auxeticity is observed in the SLS under static and low-speed impact. Within the considered impact velocity, the dynamic sensitivity of the SLS is derived from the strain rate effect of the base material. The plateau stress of SLS under dynamic loading is higher than that of the FLS, which indicates that the SLS may not be conducive to saving from harm to the protected targets under dynamic loading.